Culture first! : (Cassell, 1996)
Posing questions about the quality of life today, and our role as media consumers, this study attempts to analyze attitudes to the revolutionary changes affecting the media, encapsulated in the terms "digital revolution" and "multimedia". As individuals we are confronted with the problem of a vast expansion of choices in media consumption, and we face a new burden of aesthetic and ethical responsibility for the quality of the media we receive, and whose production we encourage. How are we to exercise that responsibility and ensure quality control? The contributors to this text attempt to show us ways in which this may be achieved.